2022
DOI: 10.1021/acsami.1c21273
|View full text |Cite
|
Sign up to set email alerts
|

Reversibly Stretchable Organohydrogel-Based Soft Electronics with Robust and Redox-Active Interfaces Enabled by Polyphenol-Incorporated Double Networks

Abstract: Hydrogel electrolytes as soft ionic conductors have been extensively exploited to establish skinlike and biocompatible devices. However, in many common hydrogels, there exists irreversible elongation upon prolonged stretching cycles and poor interfacial contact, which have significantly hindered their practical applications where long-term operation at large deformations is needed. Herein, multifunctional soft electronic devices with reversible stretchability and improved electrode/electrolyte interfaces are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…This slight change may be a consequence of the suppressed irreversible elongation after cyclic stretching (< 25% residual strain) by taking advantage of the self-recovery characteristics of the noncovalently crosslinked gel networks (Fig. S1) [ 47 ]. Impedance measurement of GEL-GLY/Na 3 Cit was further performed to determine both the internal ion conductivity and the capacitance of the solid-state electrolyte (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This slight change may be a consequence of the suppressed irreversible elongation after cyclic stretching (< 25% residual strain) by taking advantage of the self-recovery characteristics of the noncovalently crosslinked gel networks (Fig. S1) [ 47 ]. Impedance measurement of GEL-GLY/Na 3 Cit was further performed to determine both the internal ion conductivity and the capacitance of the solid-state electrolyte (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The slight change could be a consequence of the suppressed irreversible elongation after cyclic stretching (< 25% residual strain) by the self-recovery of the non-covalently crosslinked gel networks (Figure S1). [41] Impedance measurement of GEL-GLY/Na 3 Cit was further performed to determine the internal ion conductivity and capacitance of the solid-state electrolyte (Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
“…For carbon electrodes, Wang et al recently demonstrated that organohydrogels with tannic-acid-modified interfaces could enable robust adhesion of transfer printed serpentine microelectrodes to sustain thousands of stretching cycles at 100% strain, while the electrochemical capacitance could also be enhanced to ~4 folds owing to the redox activity of tannic acid. 117 In addition, the instant attachment of electrodes on prestretched hydrogels was facilitated by simply coating commercial cyanoacrylatebased adhesives, leading to tough bonding of various soft devices including integrated circuits, sensors, battery and drug-releasing device with high tension stability. 118 Alternatively, the conductive inks for fabricating microelectrodes can be directed printed onto the gel surface with stencil or ink-jet printing.…”
Section: Gel Substrates With Printed Electrodesmentioning
confidence: 99%
“… 116 The acidic solution of the Fe 3+ ‐containing precursors simultaneously promoted the rapid release of sacrificial PAA layer, accomplishing the aqueous‐phase transfer printing of polymer‐supported metal electrodes for neural interfaces. For carbon electrodes, Wang et al recently demonstrated that organohydrogels with tannic‐acid‐modified interfaces could enable robust adhesion of transfer printed serpentine microelectrodes to sustain thousands of stretching cycles at 100% strain, while the electrochemical capacitance could also be enhanced to ~4 folds owing to the redox activity of tannic acid 117 . In addition, the instant attachment of electrodes on prestretched hydrogels was facilitated by simply coating commercial cyanoacrylate‐based adhesives, leading to tough bonding of various soft devices including integrated circuits, sensors, battery and drug‐releasing device with high tension stability 118 …”
Section: Gel‐based Platforms With Spatially Patterned Inhomogeneitymentioning
confidence: 99%